PROFIL VITAMIN D PADA PASIEN ASMA DAN NON-ASMA DEWASA DI SURABAYA - Rivan Virlando Suryadinata; Amelia Lorensia; Anugrah Putri Aprilia (The Indonesian Journal of Public Health, 2017)
Asthma is a chronic inflammatory disease on respiratory tract, where airflow are retricted dan chronic inflammation result in bronchial epithelium damage. Pathogenesis mechanism of asthma is influenced by vitamin D as an immunomodulator. The low vitamin D levels can trigger asthmaexacerbations. The study aimed to determine the levels of vitamin D from blood sample in astmatic young adult in compared to non astmatics, to identify the risk of vitamin D deficiency, that can aggravate asthma symptoms. The study used an observational analytic cross sectional design. Subjects were chosenthrough a purposive sampling method. Population was young adults in Surabaya. Subjects were 26 asthmatic patientsdan 26 non-asthmatic young adult in South Surabaya that fulfilled inclusion dan exclusion criteria. The study was conducted in May 2015 to July 2016. The results showed vitamin Dlevels in the asthma group 24.5 ± 2.95 while in the non-asthma group 20.52 ± 2.47. All respondents in both groups had vitamin D levels > 30 ng/mL (normal value), dan there was significant difference between levels of vitamin D in asthma dan non-asthma patients (p < 0.05). Therefore, increasing knowledge about the importance of vitamin D should be done, because it can change behavior through lifestyle, diet dan physical activity in the community.Keywords: asthma, vitamin D